Cross-sectional return patterns in New Zealand's registered and OTC stock markets. Issue 1 (2nd February 2015) - Anderson, Hamish; Marshall, Ben; Wang, Xiao
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to examine whether the cross-sectional return patterns in New Zealand's main stock market (NZSX) are also present in the alternative (NZAX) and over-the-counter (Unlisted) markets. Design/methodology/approach – Cross-sectional regressions of monthly stock returns on well-known pricing factors including firm size, book-to-market (B/M) ratio, liquidity and past returns were run. The NZSX sample commenced in 1988 and continued through to 2011, while data are available for the Unlisted and NZAX markets from 2004 to 2011. Findings – The pricing factors that are important in explaining returns in major international markets also influence returns on the NZSX. However, only B/M is consistently priced across all New Zealand stock exchanges, including the alternative NZAX and Unlisted markets. There is evidence of reversal in NZAX stocks, but liquidity effects are not consistent or pervasive in either market. Practical implications – With B/M being the only consistently priced variable across all markets, investors in the NZAX and in particular Unlisted may be concerned with other risk factors. For example, the risks associated with differing levels of investor protection, corporate governance and disclosure may be of more concern to investors than pricing factors such as size, liquidity and past returns in these alternative trading platforms. Originality/value – The paper examines cross-sectional return patterns of the NZAX and Unlisted stocks and is the first paper to jointly test the explanatory power of size, B/M, past returns and liquidity factors for NZSX stocks.